Ecological anthropology of positive eugenics of the peoples of the East - Mirzakhmedov Abdirashid; Mirzakhmedov Khurshid; Pardaeva Sevara (BIO Web of Conferences)
This article explores human ecology as a condition for high- quality demography, regulation of the social foundations of the society of modern Central Asia, which arose the problem of improving the human race. Eugenics from Plato to F. Galton has gone through an evolutionary path of searching for the fulfilment of a social order to improve social life as a living social organism. The development of the ideology of eugenics has a negative and positive character - two opposite parallels associated with Nazi barbarism and the ethno-confessional way of family life. Based on religious and national traditions and values, the author analyses the problems of improving the quality of the population, aimed at developing a harmoniously developed generation on the example of the great ancestors of the Middle Ages. According to the author, in the traditions of the peoples of Central Asia, targeted program approaches have still been preserved to improve the quality of the population by strengthening the family and marriage, which prevents celibacy, incest, sexual lack of culture, and an increase in the number of illegitimate children. In this regard, the author puts forward the Muslim demographic development programs as a condition for the spiritual and moral stability of social life, strengthening the family and marriage as a guarantor of social progress. Modern eugenics research is research conducted to strengthen the family and marriage, to raise a physically and spiritually worthy generation. The problems and prospects of the national demographic development program in the republic should be considered in the context of the ethno- confessional organization of family and marriage life, taking into account the transformation of social trends in medical education, and the obvious problem in preventing the growth of divorces, hereditary diseases, spiritual and moral deviations in the new generation of young people.